Pemodelan Metode Time-Driven Activity Based Costing (ABC) Dalam Sistem Just-In-Time (JIT) Untuk Estimasi Biaya Produksi (Studi Kasus di Laboratorium Fakultas Teknik Universitas Merdeka Madiun) - Anisa, Nurfa (JURNAL AGRI-TEK, 2015)
Time-Driven Activity Based Costing (ABC) is a method that models the relationship between product and resources used, where the time-driver (duration) of an activity which becomes measuring rod. The purpose of this research make modeling methods Time-Driven ABC in JIT system, and then estimate the costs incurred in activities on production floor in JIT system. The research was done on production floor assembly department (assembly). Processing and analysis of data is done by identifying JIT system and calculate the estimate cost of production through a mathematical model that is commonly used in the implementation of ABC method, then modified according to conditions in rigorous object that is representation of JIT system. The result showed the estimated cost of production in shop- floor assembly process more measurable with Time-Driven ABC approach. It can be seen on Conventional ABC production processes Rp 1.900,00, while Time-Driven ABC Rp 1.663,00. Time-Driven ABC provide information about the amount of capacity utilization as indicated by used-capacity Rp 565.187,04 and unused-capacity Rp 80.182,96. Also showed the cost for each activity assembly process at family-product in JIT system based on activity cost driver rate Rp 1.584,00/menit.Keywords: Conventional ABC, Time-Driven ABC, JIT system, Activity Cost Driver